2015
DOI: 10.1007/s00216-015-8902-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minimizing amount of template by addition of macromolecular crowding agent on preparation of molecularly imprinted monolith

Abstract: One of the main challenges in the preparation of molecularly imprinted polymers (MIPs) is the substantial initial amount of template needed because of the requirement of high load capacities for most applications. A new strategy of macromolecular crowding was suggested to solve this problem by reducing the amount of template in the polymerization recipe. In a ternary porogenic system of polystyrene (PS) (crowding agent), tetrahydrofuran, and toluene, an imprinted monolithic column with high porosity and good p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…Recently, macromolecular crowding effect was found to be able to minimize the consumption of the template molecule, in imprinting procedure without obvious loss of imprinting effect . In the present study, this effect was demonstrated again.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Recently, macromolecular crowding effect was found to be able to minimize the consumption of the template molecule, in imprinting procedure without obvious loss of imprinting effect . In the present study, this effect was demonstrated again.…”
Section: Resultssupporting
confidence: 67%
“…In contrast, imprinted polymer synthesized without crowding agent, did not show any imprinting effect at so low template amount (P2, IF = 0.26), suggesting that the dramatic improvement of imprinting effect had been derived from the addition of crowding agent in the polymerization system (Supporting Information Table S1). Normally, imprinting effect decreased rapidly with decreasing the consumption of template, which could be attributed to the left‐shift of equilibrium in template and monomer after reducing the template . Prepolymerization composed of template and monomer with a lower ratio of 1:1564 was prepared and then initiated to form a MIP (P3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a high concentration of linear polymer, the formation of hydrogen bonds between the template and the monomer at the pre-polymerization stage is promoted, and thus the resultant polymers have a superior affinity or number of binding sites for the template. Although a number of crowding-assisted MIPs have been successfully developed, such as MIP monoliths [14][15][16][17][18] and microparticles, [19][20][21] the molecular crowding agents used in the literature are limited to polystyrene (PS) 14,19 and methyl methacrylate (PMMA). 13 Recently, an effect of minimizing the amount of template by addition of macromolecular crowding agents on preparation of the imprinted monolith was observed.…”
Section: Introductionmentioning
confidence: 99%